"There's plenty of room at the bottom": deep brain imaging with holographic endo-microscopy - Uhlířová, Hana; Stibůrek, Miroslav; Pikálek, Tomáš; Gomes, André; Turtaev, Sergey; Kolbábková, Petra; Čižmár, Tomáš (Neurophotonics, 2024)
SIGNIFICANCE: Over more than 300 years, microscopic imaging keeps providing fundamental insights into the mechanisms of living organisms. Seeing microscopic structures beyond the reach of free-space light-based microscopy, however, requires dissection of the tissue-an intervention seriously disturbing its physiological functions. The hunt for low-invasiveness tools has led a growing community of physicists and engineers into the realm of complex media photonics. One of its activities represents exploiting multimode optical fibers (MMFs) as ultra-thin endoscopic probes. Employing wavefront shaping, these tools only recently facilitated the first peeks at cells and their sub-cellular compartments at the bottom of the mouse brain with the impact of micro-scale tissue damage. AIM: Here, we aim to highlight advances in MMF-based holographic endo-microscopy facilitating microscopic imaging throughout the whole depth of the mouse brain. APPROACH: We summarize the important technical and methodological prerequisites for stabile high-resolution imaging in vivo. RESULTS: We showcase images of the microscopic building blocks of brain tissue, including neurons, neuronal processes, vessels, intracellular calcium signaling, and red blood cell velocity in individual vessels. CONCLUSIONS: This perspective article helps to understand the complexity behind the technology of holographic endo-microscopy, summarizes its recent advances and challenges, and stimulates the mind of the reader for further exploitation of this tool in the neuroscience research.